2019
DOI: 10.1089/tmj.2018.0113
|View full text |Cite
|
Sign up to set email alerts
|

Telelactation via Mobile App: Perspectives of Rural Mothers, Their Care Providers, and Lactation Consultants

Abstract: Among rural women who experience inequitable access to qualified breastfeeding support resources, DTC telelactation appears to be an acceptable delivery model for lactation assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 17 publications
4
36
0
6
Order By: Relevance
“…The third cluster comprises 7 papers [54-59,61] discussing 6 interventions that facilitate communication between peers and professionals. Of the systems, 3 [55-57] provided tele-lactation consultations via video conference for mothers with limited access to maternal care. Giglia et al [59] designed a multichannel support intervention through focus group; the intervention provides lactation supports through Web-based resources, email, and video call, all at the same time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third cluster comprises 7 papers [54-59,61] discussing 6 interventions that facilitate communication between peers and professionals. Of the systems, 3 [55-57] provided tele-lactation consultations via video conference for mothers with limited access to maternal care. Giglia et al [59] designed a multichannel support intervention through focus group; the intervention provides lactation supports through Web-based resources, email, and video call, all at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…Telemedicine came in forms of remote lactation consultation via video calls [55-57] and email communication [58]. All 3 identified video-call interventions [55-57] took place in the United States, which has a geographically dispersed population.…”
Section: Resultsmentioning
confidence: 99%
“…Telelactation by mobile application "Pacify" used in some Women, Infants, and Children (WIC) nutrition program centers in the United States have shown positive results in terms of breastfeeding duration and exclusivity (Hunt, 2018). Results reported by researchers using the same telelactation application in Pennsylvania illustrated that participants were content with the care they received, which was associated with increased breastfeeding confidence (Demirci et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…A content analysis developed by Schindler-Ruwisch et al 37 identified that, just like mobile applications, text messaging is a potentially far-reaching resource in providing information about breastfeeding. 38 Austen et al 39 present the use of video with musical parody as an additional resource to sensitize young adults about the importance of breastfeeding. These seem to be signs that health education must adhere to the trend of innovation.…”
Section: Alam Et Al (2017)mentioning
confidence: 99%